Basic Concepts of Educational Institution Management: The Main Foundation in Developing The Quality of Education - Nurhikmah, Nurhikmah (Insight: Indonesian Journal of Social, Humanity, and Education, 2025)
Management skills are needed to provide quality education. The abilities and knowledge needed by an educational manager to carry out management tasks and functions are known as management skills. This study aims to improve knowledge about the basic concepts of educational management. This study combines theory and practice about the concept of management that is very important in the world of education. In this paper, using a library approach (library research) using qualitative descriptive methods and data collection is carried out by reviewing and exploring a number of articles, books, documents, and other information that is relevant to the theme discussed. The results of the research from this journal are that every educational institution must have management and educational staff to carry out the education and management process. Therefore, it is very important to know how management and educational staff function so that educational institutions can run well and with quality.